INHERITANCE OF RESISTANCE TO BROWN BLOTCH DISEASE OF COWPEA - OBISESAN, I. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The inheritance pattern of resistance to brown blotch disease of cowpea was investigated by using crosses involving two resistant (Hope, Crimson) and two susceptible (Ife Brown, Ife Branched Peduncle) parents. The F1 data indicated that resistance was dominant over susceptibility. Segregation patterns in the F, and backcross generations of all crosses showed a good fit to a 15 resistant: I susceptible ratio suggesting that two duplicate dominant genes condition resistance to brown blotch disease. Furthermore, since segregating populations or reciprocal as well as non-reciprocal crosses gave similar ratios, it was concluded that the two dominant genes which condition resistance were nuclear genes.